Memori Kolektif Melalui Komunikasi Konteks Arsitektural - Yusran, Yusfan Adeputera; Ineru, Bunga Pasadena (Hasta Wiyata, 2025)
The Rupiah banknotes are visual cultural objects with the ability to present visual narratives that evoke collective memory. The Rupiah banknotes issued between 2000 and 2005 maintain a consistent design pattern across all denominations, featuring national heroes on the front and local identities on the back, which represent the rich history and culture of Indonesia. Research on visual culture focusing on collective memory in the context of architectural communication is still limited. This study employs architectural criticism methods to examine and critique the role of visualizing local identity in revealing collective memory related to historical context and its implications for architectural communication, grounded in the concept of visual culture. The visualization of local identity elements depicted on the Rupiah banknotes from 2000 to 2005 in each denomination serves as an architectural representation that can shape communication in the form of collective memory, narrating cultural identity and leading to architectural context. The results of this study, through the analysis of architectural object representation, can enrich understanding related to visual culture and its connection to the presence of collective memory concerning local identity.